THE INTEREST OF PAKISTAN JOIN THE SHANGHAI COOPERATION ORGANIZATION (SCO) - Rizky Kurniawan Pratama; Mhd. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to explain Pakistan's interest in joining the Shanghai Cooperation Organization (SCO). Pakistan's entry into the Shanghai Cooperation Organization (SCO) is optimistically seen as a turning point in a changing geopolitical landscape and brings new opportunities for Pakistan. Full SCO membership provides an opportunity for Pakistan to cooperate and increase bilateral as well as multilateral trade. This research theoretically built using a neoliberalism perspective and supported by the theory of International Cooperation from KJ. Holsti. The formulation of all arguments, data, methods, and theoretical framework in this study uses a qualitative explanation. This study also uses the nation-state as its level of analysis. The result of this study indicates that SCO's importance to Pakistan based on the reality of Pakistan's goal as a potentially viable trade corridor with the landlocked countries of Central Asia and Xinjiang in the West China region. SCO is also a convergence of geo-economic interests between Pakistan and China which basically complement each other's geo-strategic interests. The idea of Pakistan as a trade and energy route stems from its vital geographic location. Given Pakistan's significant geographic location, it can be observed that Pakistan is the natural territory of the SCO cooperation structure and is ideally located to provide a link for regional economic integration within and between SCO member countries. Keywords: SCO, Gwadar Port, CARs, geo-strategic interests